Rice Marketable Surplus, Marketed Supply And Its Determinant Factors In Mukomuko District - Hari Mustamam; Ketut Sukiyono; Nusril Nusril (Journal of Agri Socio Economics and Business, 2019)
This research aims to estimate the marketable surplus and marketed supply of rice in Mukomuko Regency.  This research is also aimed at identifying determinant factors of marketed supply and predicting rice availability in Mukomuko Regency. Data collected were primary and secondary data. The research location is determined using a cluster sampling method with 130 respondent selected using Stratified random sampling. The data analysis was used quantitative descriptive and regression analysis estimated. The result shows that percent marketable surplus and marketed supply of rice is 83.43% and 85.27 per ha per planting season respectively. The factors influencing the marketed supply of rice is Rice production and price. The rice availability from 2017 to 2020 is projected to increase by 44.56%.  Consumption is projected to increase by 20.407 Kg in 2020. For the next 5 years, i.e.,2018-2022, rice availability and surplus positively increase.